Export practice and documentation - Walker, Alexander George (Butterworths LondonGB, 1987)
Guide to the mass of detailed procedures and regulations with which the exporter needs to be familiar - including shipping documentation, distribution and packing, invoicing, credit facilities and insurance. Also discusses international marketing and export management administration.